OPTICAL AND SPECTROSCOPIC PROPERTIES OF Er3+DOPED 60Sb2O3-10Na2O-30PbO GLASS - MANCER, MANSOURA; SOLTANI, MOHAMED TOUFIK (Courrier du Savoir; No 26 (2018): Courrier du Savoir, 2018)
Er 3+ doped sodium lead antimonite glass have been prepared and analyzed by (UV-Vis-NIR) absorption, near infrared luminescence and fluorescence decays. The optical band gap and refractive index were calculated from the (UV-Vis-NIR) absorption. The Judd-Ofelt theory has been applied to compute the J–O intensity parameters Ωt (t= 2, 4, 6) from absorption spectrum and determine the spectroscopic parameters such as the radiative transition probability (A rad ), radiation lifetime (τ) and branching ratio (β) of Er 3+ transition. Experimental lifetime of the glass for the transition between 4 I 13/2 and 4 I 15/2   level was calculated from the photoluminescence decay curves and estimated the quantum efficiency. Absorption, emission and gain cross-section, effective band width (Δλ eff ) and gain band width of the 4 I 13/2 ® 4 I 15/2   transition of Er 3+ in glass are recorded and calculated. The obtained results confirm the potential of this glass in signal amplification and laser application.